Effect of Antiplatelet Medications on Critically Ill Patients with Pre-existing Atrial Fibrillation - Alqadi, Mohammad (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.